How to Introduce Jazz to Children - Bauer, Val (Širjenje obzorij o poučevanju glasbe, 2025)
This chapter describes the representation and role of jazz in the elementary school curriculum. Jazz is not sufficiently represented in elementary schools, which is why this chapter offers various brief descriptions of how jazz can be incorporated into the teaching process and highlights the benefits of its inclusion. The chapter outlines two approaches a teacher could take to teach jazz. The first approach involves using jazz as repertoire, while the second involves using jazz as a vehicle for teaching broader musical concepts. Additionally, this chapter raises the question of whether children truly understand jazz and, more importantly, whether teachers understand jazz. The latter is particularly significant as it indirectly influences the quality of the teaching process. The primary goal of this chapter is to propose the inclusion of jazz at an early stage of elementary school education, enriching the musical experience of young children.